An Appraisal of Digital Storytelling in English Language Learning - Moyo, Rachel (Studies in Learning and Teaching, 2024)
The movement restrictions imposed by governments due to the COVID-19 pandemic in early 2020 challenged the status quo in education and will likely see traditional methods of teaching waning. The unprecedented shift to online instruction pronounced the fourth education revolution, particularly in developing economies, amid the fourth and in some parts, the fifth industrial revolution, a world seized by digital technologies. The current study sought to appraise digital storytelling as a teaching strategy in English second language learning, motivated by the noted generally poor performance in the subject. A literature review of empirical findings on digital storytelling in English language learning was conducted based on their availability. The review findings reveal a consensus among researchers that the language competence of learners taught using digital storytelling improved compared to traditional methods across grade levels from primary to high school levels. To this end, a digital storytelling model for language learning was developed, indicating the challenges faced by the learners and how digital storytelling can be used to scaffold the understanding of these concepts. Education departments should invest in hardware and software for innovative, digital teaching methods to improve learning and to keep abreast with advancing technologies.